对中国国有企业改革的再思考 = China's SOEs : problems and solutions - Yang, Qinglong (2008)
While the reform of the state-owned sector in China has been the key to the entire reform process, there still have been serious challenges facing the state-owned enterprises (SOEs) and the Chinese government. With the problems of a huge loss, assets depreciation and depletion, and a high debt ratio in the state-owned sector, a more fundamental solution needs to be found for the SOEs.